Exploring the Role of Victim Sex, Victim Conduct, and Victim–Defendant Relationship in Capital Punishment Sentencing. (May 2014) - Gillespie, Lane Kirkland; Loughran, Thomas A.; Smith, M. Dwayne; Fogel, Sondra J.; Bjerregaard, Beth
Disparities in the administration of capital punishment are a prominent social and political issue. Recent studies indicate that victim characteristics of sex and race produce interactive effects on capital-sentencing outcomes. Extending this line of research, the current analysis explores the intersection of victim sex with victim conduct and victim–defendant relationship, utilizing a population of North Carolina capital cases spanning the years 1977 to 2009 ( N = 1, 285). Findings indicate that cases with a female victim who was not involved in illegal activity at the time of the murder and acquaintance female victim cases are most likely to result in a death recommendation. Potential reasons for these findings are discussed.